The Green Path to Satisfaction: Examining the Relationship of Nature Connectedness and Resilience with Life Satisfaction among Youth - Prof. Vishva Chaudhary, Himanshi Chhatwani, Kriti Shandilya (South Eastern European Journal of Public Health, 2025)
This study explores the relationship of nature connectedness and resilience with life satisfaction among youth in India. Sample of 143 youth (aged 18-24) was surveyed using the Connectedness to Nature Scale, Brief Resilience Scale, and Satisfaction with Life Scale. Findings suggested that nature connectedness and resilience, were positively correlated with life satisfaction and collectively significantly predicted 33% of the variance. Resilience had a stronger predictive value compared to nature connectedness. The results contribute to understanding how psychological and environmental factors interact to promote well-being, offering insights for mental health interventions aimed at improving life satisfaction through resilience-building and nature engagement